Technological properties of the protein-polysaccharide complex from the mushroom Pleurotus ostreatus - Mansky, Olexandr; Sayko, Irina; Sichkar, Antonina (Annals of Mechnikov's Institute, 2022)
Introduction. A balanced intake of the main food substances — proteins, carbohydrates, fats, vitamins and minerals — creates conditions for physical and mental development, supports high productivity, increases the body's protective function, and helps prevent stressful conditions and many diseases. The valuable product is the oyster mushroom (OM, lat. Pleurotus ostreatus), fruit bodies of which contain vitamins (thiamine, riboflavin, niacin, biotin, ascorbic acid, pantothenic acid, calciferol, tocopherol, ergosterol), amino acids (tryptophan, cystine, aspartic acid, lysine, alanine, etc.), minerals (iron, phosphorus, potassium), polysaccharides and phytosterols. One of the most common ways to solve the problem of food imbalance is the additional use of a sufficient number of necessary biologically active substances in the form of special food additives as dietary supplements. The article is devoted to the study of the technological properties of the water-soluble protein-polysaccharide complex (WSPPC) from the fungus Pleurotus ostreatus to create a dietary supplement based on it to correct the diet of patients with dyslipidemia and atherosclerosis. The purpose of this work was obtaining WSPPC from the mushroom Pleurotus ostreatus and studying technological properties of WSPPC for further development of a dietary supplement with it. Materials and methods. When conducting research, we used generally accepted research methods according to the State Pharmacopoeia of Ukraine. The object of research was the dried, crushed and sifted fruit bodies of the oyster mushroom. WSPPC has been obtained by extracting the prepared fruit bodies with purified water at a temperature of 50 oC. The ratio of raw materials to extractant was 1 : 15. The extraction method was a three-stage remaceration, which lasted 90 minutes. The obtained extract has been partially evaporated and precipitated with three times the amount of 96 % ethanol. The supernatant has been separated after two hours of extract settling. The wet precipitate has been dried at a temperature of 50 °C to a residual humidity of 4-5 %. The resulting dry powder of WSPPC has been crushed. The final conclusions were made based on five repeated measurements that provide reliable data. Results and discussion. According to the microscopic analysis it was established that the powder particles WSPPC from fruit bodies of mushroom Pleurotus ostreatus have a smooth surface and a plate-like shape. WSPPC powder has the largest fraction with particles of 0.3-0.5 mm, which is usually well dosed by volume. According to the technological studies, the samples of WSPPC have a good flowability. The values of the Carr index, the Hausner ratio and angle of repose make it possible to conclude that there is not a large force of cohesion between the particles. The difference between the bulk density of the substance and tapped density after shrinkage showed the ability to shrink. The kinetics of moisture absorption was investigated. The WSPPC powder may absorb moisture and can be classified as hygroscopic. Therefore, when developing of a dietary supplement, it is necessary to introduce moisture regulators to the composition for the stability of WSPPC during storage. Conclusion. The results of the studies indicate that the WSPPC powder have satisfactory parameters of the technological properties and such results can be used in the development of technology of a dietary supplement with lipid-lowering and antioxidant action in the form of a solid dosage form. Key words: water-soluble protein-polysaccharide complex, oyster mushroom, technological properties, dyslipidemia, atherosclerosis, dietary supplement.